Post-traumatic nail pterygium. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2018)
The nail pterygium is a cutaneous branch that starts from the skin of the matrix and protrudes on the nail plate making disappear the proximal nail fold. Pterygium follows a violent inflammation that results in a fibrotic process leading to the fusion between the nail fold and the underlying nail bed. The fibrotic band prevents the normal growth of the nail plate which then appears dystrophic or is completely destroyed (2). Lichen planus is the disease most frequently associated with pterygium (1). However, the latter has also been described in association with systemic sclerosis, graft versus host disease, leprosy, porokeratosis, trachyonychia, sarcoidosis and autoimmune bullous disorders; the traumas can be reponsible for pterygium as in the actual case; however, there is also an idiopathic form in which no obvious cause can be found. Early systemic corticosteroid therapy is the most effective.